Diseases of cumin (Cuminum cyminum L.) and their management - DANGE, S R S (Journal of Spices and Aromatic Crops, 1995)
Cumin (Cuminum cyminum L.) is affected by wilt, blight and powdery mildew diseases which are responsible for heavy yield losses. Witches - broom, probably caused by MLO, has also been reported from Rajasthan. The symptoms of these diseases and management schedules to be adopted are discussed.